Answering Causal Questions: Angrist, Imbens and the Nobel Prize. Issue 6 (28th November 2021) - Mealli, Fabrizia
Abstract: This year's Nobel Prize in Economic Sciences was awarded to David Card, Joshua Angrist and Guido Imbens for their research showing how natural experiments can be used to answer causal questions. Card was cited for his "empirical contributions to labour economics", while Angrist and Imbens were cited for their "methodological contributions to the analysis of causal relationships". Here, Fabrizia Mealli explains the work of Angrist and Imbens, and how it has helped to transform the study of key policy questions in areas including education, immigration and labour markets